Market Competence of BSNL in the Present Dynamic Telecom World - M., Amulya; D., Anand (Indian Journal of Marketing, 2011)
The Telecom market in India is 2nd in the world after beating USA and trailing only after China. The global meltdown did not affect the telecom market world wide. While the market is making high profit, competitors are expanding their business, and going international. The Indian telecom behemoth, which once upon a time was the largest telecom player in the country, BSNL is seeing its market share and revenues shrink even as the telecom market grows rapidly. Inspite of having many strengths, which private players cannot even think of, BSNL is facing many problems after the entry of the private players into Indian telecom market, which needs to be addressed to wake up to the sleeping giant to regain its position as a market leader. This article makes a brief overview of the Indian telecom market, analyses the facts concerned with reference to BSNL in the present situation. The paper also suggests a long term solution to sustain the market pressure and to regain the past glory.